2016
DOI: 10.1161/strokeaha.115.011187
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Permeability Is Associated With Improved Functional Outcome and Recanalization in Patients With Ischemic Stroke

Abstract: T reatment of patients with acute ischemic stroke (AIS) is aimed at reopening occluded arteries and reestablishment of intracranial perfusion. Determining pivotal characteristics about the occluding thrombus using available imaging has the potential to improve patient's diagnostics and prognostics.Background and Purpose-Preclinical studies showed that thrombi can be permeable and may, therefore, allow for residual blood flow in occluded arteries of patients having acute ischemic stroke. This perviousness may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 26 publications
7
100
2
Order By: Relevance
“…13 Location of the thrombus (M1, M2, A1, A2, ICA, or ICA-T) was determined on CTA by expert neuroradiologists. 1 The length of the thrombus was measured on NCCT with the aid of coregistered CTA, with an inhouse-developed MeVisLab interface (www.mevislab.de).…”
Section: Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…13 Location of the thrombus (M1, M2, A1, A2, ICA, or ICA-T) was determined on CTA by expert neuroradiologists. 1 The length of the thrombus was measured on NCCT with the aid of coregistered CTA, with an inhouse-developed MeVisLab interface (www.mevislab.de).…”
Section: Image Analysismentioning
confidence: 99%
“…Density measurement of the thrombus and contralateral vessel segment was performed on NCCT and coregistered CTA by a trained observer (M.d.B., with 1 year of experience), blinded to clinical information, with the in-house-developed MeVisLab interface. 13 The mean thrombus density was calculated by averaging the Hounsfield units of 3 manually placed ROIs of the thrombus. Relative density was calculated by dividing the mean Hounsfield unit of the thrombus by the mean Hounsfield unit of the contralateral vessel segment.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, thrombus perviousness as evidenced by higher clot density is strongly associated with recanalization after intravenous recombinant tissue‐plasminogen activator (rt‐PA) treatment and favorable functional outcome 3. Our study disclosed that MCA clots in the context of terminal ICA occlusion differ in terms of density based on the presence of proximal collateral flow.…”
Section: Discussionmentioning
confidence: 75%
“…Understanding the composition of the thrombus may provide additional information to determine the potential success of reperfusion efforts and individual prognosis. Several studies confirmed that a higher thrombus density is associated with improved reperfusion rates and better outcome, regardless of systemic or endovascular recanalization techniques 3, 4, 5, 6. Thrombus density can be determined noninvasively on noncontrast enhanced CT (NECT) and was shown to be dependent on source, time, and hematocrit, and is altered by treatment with antiplatelets 7, 8.…”
Section: Introductionmentioning
confidence: 99%